VEHICLE TAX AS AN INSTRUMENT OF PRICE COMPETITIVENESS FOR CARRIERS IN THE EU (Perner's Contacts, 2018)
There are many factors to make the price of road freight transport. A transport company that has been defined as the main business aktivity like a mediation of the transport of goods and services, has a difficult position to succeed in the market, where many companies have the same focus. It is the transport price that is important for the customer, for which the shipment is carried out. Being a transport company, the cheapest for the customer, that means getting it to carry out the transport. In this article the authors look at one of the tools more specifically, which acts on the price of making the price in road freight transport, namely the tax on motor vehicles, through which some carriers can be more competitive as other carriers on the EU transport market.
Keywords: vehicle tax, carriers, costs